The art of startup fundraising : pitching investors, negotiating the deal, and everything else entrepreneurs need to know - Cremades, Alejandro (John Wiley & Sons, Inc., 2016)
"Startup money is moving online, and this guide shows you how it works. The Art of Startup Fundraising takes a fresh look at raising money for startups, with a focus on the changing face of startup finance. New regulations are making the old go-to advice less relevant, as startup money is increasingly moving online. These new waters are all but uncharted--and founders need an accessible guide. This book helps you navigate the online world of startup fundraising with easy-to-follow explanations and expert perspective on the new digital world of finance. You'll find tips and tricks on raising money and investing in startups from early stage to growth stage, and develop a clear strategy based on the new realities surrounding today's startup landscape. The finance world is in a massive state of flux. Changes are occurring at an increasing pace in all sectors, but few more intensely than the startup sphere. When the paradigm changes, your processes must change with it. This book shows you how startup funding works, with expert coaching toward the new rules on the field. Learn how the JOBS Act impacts the fundraising model Gain insight on startups from early stage to growth stage Find the money you need to get your venture going Craft your pitch and optimize the strategy Build momentum Identify the right investors Avoid the common mistakes Don't rely on the "how we did it" tales from superstar startups, as these stories are unique and applied to exceptional scenarios. The game has changed, and playing by the old rules only gets you left behind. Whether you're founding a startup or looking to invest, The Art of Startup Fundraising provides the up-to-the-minute guidance you need"--